INCEST AND CULTURAL VALUES IN ARUNDHATI ROY’S THE GOD OF SMALL THINGS (1997): A SOCIOLOGICAL APPROACH - HARTINI, HARTINI (2011)

(untitled)
The object of the research is a novel entitled The God of Small Things written by Arundhati Roy. The study focuses on the sociological aspect of the novel. The major problem of this study is to depict how is Incest and Cultural Values reflected in Arundhati Roy’s The God of Small Thing novel? The objectives of the study are to analyze the structural elements of the novel and to analyze the novel based on the sociological perspective. This research is the qualitative approach. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the novel itself. The method of the data collection is documentation research. The technique of data analyzes is descriptive analyzes. The results of the research show the following conclusions. Firstly, based on the structural analysis, Arundhati Roy wants to deliver a message to the reader that incest or the forbidden love in The God of Small Things occurs because of social contexts. Secondly, based on the sociological analysis it shows that Arundhati Roy reflects the people in that time were still living under colonial rule and the caste system.